The fate of coracoid graft after Latarjet procedure: arthroscopic and open findings of graft union and glenoid remodelling - Mohd Nasir, Mohd Nizlan; Yeak, Raymond Dieu Kiat; Rashid, Ahmad Hisham (Journal of the College of Physicians and Surgeons Pakistan, 2021)
Successful Latarjet procedures depend on many factors including graft union and subsequent restoration of the glenoid surface. Coracoid graft union has been studied; however, remodelling of the glenoid has not been studied extensively. We present two Latarjet cases in which coracoid screws were removed due to hardware issues, at 12 months postoperatively in one patient and at six months in another. We share our observations on the coracoid graft and the restoration of the glenoid shape. Prior to screw removal, done by a mini-open approach, we performed arthroscopic examination of the glenohumeral joint in both patients. Our arthroscopic and open findings with respect to graft union, screw prominence, and glenoid remodelling, are presented. Both cases showed good union of the coracoid graft and restoration of the native glenoid shape.